2010
DOI: 10.1152/ajplung.00217.2010
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of plasma membrane wounding by deforming stress

Abstract: Once excess liquid gains access to air spaces of an injured lung, the act of breathing creates and destroys foam and thereby contributes to the wounding of epithelial cells by interfacial stress. Since cells are not elastic continua, but rather complex network structures composed of solid as well as liquid elements, we hypothesize that plasma membrane (PM) wounding is preceded by a phase separation, which results in blebbing. We postulate that interventions such as a hypertonic treatment increase adhesive PM-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…This hypothesis, however, remains elusive as long as vital lung microscopy, employing sophisticated techniques, will allow it to be proven or disproven (41,66). In contrast to this hypothesis, experiments provided evidence that interfacial stress is a determinant of cell wounding in pathophysiological settings, e.g., in surfactant-compromised lungs or as a consequence of alveolar edema (9,48).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis, however, remains elusive as long as vital lung microscopy, employing sophisticated techniques, will allow it to be proven or disproven (41,66). In contrast to this hypothesis, experiments provided evidence that interfacial stress is a determinant of cell wounding in pathophysiological settings, e.g., in surfactant-compromised lungs or as a consequence of alveolar edema (9,48).…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar cells, an element of the blood-gas barrier, also have a critical role in determining the homeostatic balance of pulmonary interstitial fluids during stress. Because alveolar cells are not elastic, Oeckler et al (31) showed that plasma membrane-cytoskeletal adhesive interactions are important determinants of the cellular response to deforming stress. Caveolar endocytic response to transient actin remodeling following deformation of plasma membrane increases cell permeability in both alveolar (15,49) and endothelial cells (26) in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Using a similar rigid airway model, Yalcin et al (48) demonstrated that the degree of cell injury during cyclic airway closure/reopening is inversely proportional to airway diameter, and that changes in the cell's cytoskeletal structure can be used to mitigate cell injury during reopening (47). Similarly, Oeckler et al (35) demonstrated that hypertonic treatment reduces cell injury by increasing plasma membrane-cytoskeleton adhesive interactions. Although these results indicate that altering cell mechanics represents a novel way to reduce atelectrauma, the in vitro models used in these studies do not take into consideration the compliant nature of lung tissue.…”
mentioning
confidence: 99%